CHANGES OF MITOCHONDRIAL FUNCTIONS IN DIFFERENT LIVER PATHOLOGIES (TOXIC HEPATITIS) - Yoqubova Nargiza Abdurasul kizi; Chuliyev Ikrom Ne’matullayevich (Journals Park Publishing, 2022)
According to the literature, mitochondrial dysfunction is the main cause of pathological conditions. Damage to the mitochondrial membrane leads to disease. For example, mitochondrial disorders in cells cause diabetes. Mitochondria are also affected by ischemia, hepatitis, and ischemic tissue reperfusion, which is manifested in the heart, brain, and kidneys. Mutations in mitochondrial proteins occur in a variety of pathological tissues; mitochondrial dysfunction is associated with all major neurodegenerative diseases such as Parkinson’s, Alzheimer’s, and impaired motoneurons, often leading to sclerosis. Cardiac mitochondrial dysfunction can lead to cardiomyopathy. Mitochondrial dysfunction has been shown to play a key role in many organ system disorders during sepsis. Mitochondria are the main target in the onset of cell dysfunction.